Isabel "Lefty" Alvarez : The Improbable Life of a Cuban American Baseball Star - Williams, Kat D. (Book collections on Project MUSE., 2020)
"Kat D. Williams traces Isabel "Lefty" Alvarez's life from her childhood in Cuba to her reinvention of herself as a professional American baseball player, illuminating the importance of sport as a source of stability in a life defined by challenges"--